Daily Temperature Effect on Seedling Growth Dynamic of Three Invasive Alien Species - Pepe, Maria; Gratani, Loretta; Crescente, Maria Fiore; Puglielli, Giacomo; Varone, Laura (Frontiers in Plant Science, 2022)
A greater Relative Growth Rate (RGR) scale positively with a species’ ability to deploy a larger leaf area either due to a greater total number of leaves in the canopy (LN) and/or due to a larger size of individual leaves (LA). The present study aimed to analyse and compare: (1) the temporal (i.e., daily) RGR, leaf production rate (LPR), and leaf area production rate (LAPR) changes during the early growth stages of three amongst the most invasive species in the world, namely Ailanthus altissima (Mill.) Swingle (AA), Phytolacca americana L. (PA), and Robinia pseudoacacia L. (RP) (2) the interspecific differences in the relationship between RGR, LPR, LAPR and mean daily air temperature. Our results show that growth dynamics as a function of temperature differ between invasive alien species (IAS). While these differences are partly explained by differences due to the growth form of the investigated species, the three IAS have a different behaviour to adjust RGR, LPR and LAPR with air temperature changes even within the same growth form, and in agreement with species habitat requirements in their native range. In conclusion, the results help disentangle the role of RGR, LPR and LAPR for non-native species in coping with air temperature changes.